Transjugular Intrahepatic Portosystemic Shunt for Refractory Variceal Bleeding in a Patient with a Left Ventricular Assist Device. Issue 1 (2018) - Thomas, Anusha Shirwaikar; Estep, Jerry; Victor, David W.
ABSTRACT : N/A: Transjugular intrahepatic portosystemic shunt (TIPS) is an attractive therapeutic option in cirrhotic patients with recurrent variceal bleeding refractory to medical and endoscopic therapy. There is little known about the use of TIPS in patients with left ventricular assist devices (LVAD). We describe a patient with a durable continuous‐flow LVAD and concurrent decompensated cardiac cirrhosis who underwent successful TIPS placement for recurrent variceal bleeding. The patient has had no rebleeding or encephalopathy in >12 months since TIPS placement.